Introduction of ABPM devices in India by Durapid Medical: Business plan - Menezes, Karla (2012)
Hypertension is an important public-health challenge worldwide, as during the past decade it has been escalating rapidly and affecting both male and female populations of all ages from developed to developing countries. Over the last century in India, numerous studies on hypertension have been conducted and the results have been remarkable. In India, hypertension was once known as the affluent / rich person’s disease, however today it is a common ailment among the rural population and even among the poor. Presently in India, the only methods for detecting and monitoring hypertension are through the conventional in-clinic or home self-monitoring devices. Both these methods utilize either the auscultatory and/or oscillometric technique for providing one-off measurements. Prevention, detection, treatment, and control of hypertension and its consequent complications should receive the utmost priority. This is a business plan for Durapid Medical to design, test, accredit and supply an innovative 24-hour Ambulatory Blood Pressure Monitoring (ABPM) device in India. Durapid Medical predicts this project to be a good investment with a positive Net Present Value (NPV) and is certain that the innovative 24-hour ABPM will be the preferred choice among doctors, physicians and hospitals for monitoring blood pressure in India.